Long-term sequelae of acute respiratory distress syndrome caused by severe community-acquired pneumonia: Delirium-associated cognitive impairment and post-traumatic stress disorder. Issue 6 (June 2018) - Denke, Claudia; Balzer, Felix; Menk, Mario; Szur, Sebastian; Brosinsky, Georg; Tafelski, Sascha; Wernecke, Klaus-Dieter; Deja, Maria
Objective: Delirium in critically ill patients is considered a risk factor for various long-term consequences. We evaluated delirium and associated long-term outcomes in patients with acute respiratory distress syndrome with non-H1N1 and H1N1- associated severe community-acquired pneumonia (sCAP) who had been recommended to take antiviral drugs associated with delirious symptoms as adverse effects. Methods: Of 64 patients, 42 survivors (H1N1, 15; non-H1N1, 27) were analyzed regarding the relationship between medication and the duration of delirium in the intensive care unit. During follow-up (n = 23), we assessed cognitive abilities, post-traumatic stress disorder (PTSD), physical capacity, and health-related quality of life (HRQoL). Results: The incidence of delirium was 88%. There was no difference in the incidence and duration of delirium between patients with H1N1 and non-H1N1 infection. The haloperidol and opioid doses were associated with a longer delirium duration. The delirium duration was correlated with reduced cognitive performance in motor skills, memory function, and learning efficiency. Patients with PTSD (16%) had a significantly longer delirium duration and low mental HRQoL. Conclusions: H1N1 infection and corresponding antiviral medication had no impact on delirium. The duration of delirium in these patients was associated with impairments in various outcome parameters, illustrating the burden of sCAP.